The Impact of Uncertainty Created by Global Factors on Fertility Decisions - Norgėlaitė, Alina (Socialinė teorija, empirija, politika ir praktika, 2022)
The article discusses the effect of global factors – COVID-19 pandemic, war in Ukraine, climate change – that form uncertainty which affects the decision to have children. The aim is to reveal the impact of uncertainty based on the results of the qualitative survey. In 2021–2022 thirty semi-structured interviews were conducted with informants born between the years 1970 and 1989. The research showed that global factors are not relevant when considering children, with climate change being the least understood and influential factor. However, the uncertainty caused by the pandemic and war, which increased uncertainty and prompted a delay in the decision to have children, had a stronger effect in the beginning and lessened with time. The pandemic was associated with the limited availability of medical services, while the reaction to war depended on personal perception of the direct threat. Older generations being close to the end of reproductive age, and younger generations having the desired number of children felt more uncertain about childbearing possibilities. A critical factor that reduced uncertainty was a strong desire to have children. Possessed information and distrust in public institutions appeared to be also quite important.
Keywords: birth; uncertainty; climate change; war; pandemic